Cloning of genes that encode transcription factors that bind to the floral Chitinase gene (CHi2;1) promoter of tomato using the yeast one-hybrid system - Chan, Pick Kuen (2003)
Flowering plays an essential role in the plant's reproductive system and so has generated considerable research interest. Both the production and correct functioning of floral tissues are a prerequisite for the formation of seeds and fruits in all economically important agronomic and horticultural plants. Many flower-specific genes have been isolated and identified. Elucidation of the mechanisms that control flower-specific gene expression has led to the identification of their regulatory elements. These elements are useful for targeting other genes to floral organs at specific times during development. Targeting gene activity to specific floral tissues without affecting other portions of the flower is a very powerful tool for basic and applied studies. The ability to target specific gene expression is essential for discovery of function other related genes and for the selective manipulation of the flower. Some of the interesting characters for manipulation include reduced pollen allergenicity, increased flower longevity and flower numbers, and modified flower architecture. Previously, a promoter region of a tomato stylar endochitinase, Chi2;1 gene had been isolated (Harikrishna et al., 1 996) and demonstrated to drive high level of expression in the pistil of transgenic plants. Hence, this study has been tailored to isolate the transcription factors that bind to the Chi2; 1 promoter and to identify specific binding regions within the promoter responsible for its binding. The yeast one-hybrid system approach was used to isolate transcription factors that recognize elements within the Chi2;1 promoter. Out of 6.17 x 106 yeast transformants screened, thirteen putative positive clones were identified and isolated based on positive ..-galactosidase assays. The DNA sequence of these clones was determined and compared to known DNA sequences in the GenBank database. Most of these clones did no have any significant homology with any known functional genes. Expression studies were conducted on three clones, with two clones, LN2-1- 1 and LN2-3-1 isolated from the -446 to -680 promoter region of Chi2; 1 and one, 90-2-1 from the -211 to --445 region of the Chi2;1 promoter. LN2-1-1 and 90-2-1 are predominantly expressed in pistils at anthesis with lower expression in petals. Meanwhile, the expression of LN2-3-1 was detected in both vegetative and floral organs. The temporal and spatial expression patterns of LN2-1-1 and 90-2-1 were similar to Chi2; 1 (Harikrishna et al., 1996). In situ hybridization of the LN2-1-1 and 90-2-1 clones revealed that the mRNA of both genes were localized to the transmitting tissue of the mature tomato pistil as with the mRNA of the Chi2; 1 gene (Gasser et aI., 1989). The binding ability of the proteins encoded by both of these genes to the respective DNA sequences has been shown through a mobility shift assay. Furthermore, the protein encoded by 90-2-1 has been shown to localize to the nucleus and bind specifically to a 20 base pair sequence within the Chi2; 1 promoter. These results suggest that both LN2-1-1 and 90-2-1 might interact with the Chi2; 1promoter region and influence Chi2; 1 gene expression to a certain extent. However, the functions of these genes in mediating style-specific expression is still to be confirmed by transgenic analysis.